Imaging neurodegeneration in the mouse hippocampus after neonatal hypoxia–ischemia using oscillating gradient diffusion MRI. Issue 3 (4th October 2013) - Aggarwal, Manisha; Burnsed, Jennifer; Martin, Lee J.; Northington, Frances J.; Zhang, Jiangyang
<x xml:space="preserve">Abstract</x> Purpose To investigate if frequency‐dependent contrasts using oscillating gradient diffusion MRI (dMRI) can detect hypoxia–ischemia (HI) ‐induced neurodegeneration in the neonatal mouse hippocampus. Methods Pulsed‐ and oscillating‐gradient dMR images (at 50, 100, and 150 Hz) were acquired from postmortem fixed brains of mice exposed to neonatal HI using the Rice‐Vanucci model. MRI data were acquired at 1, 4, and 8 days following HI, and compared with histological data from the same mice for in situ histological validation of the MRI findings. Results The rate of change of apparent diffusion coefficient with gradient frequency (ΔfADC) revealed unique layer‐specific contrasts in the neonatal mouse hippocampus. ΔfADC measurements were found to show a significant decrease in response to neonatal HI injury, in the pyramidal (Py) and granule (GrDG) cell layers compared with contralateral regions. The areas of reduced intensity in the ΔfADC maps corresponded to regional neurodegeneration seen with H&E and Fluoro‐Jade C stainings, indicating that alterations in ΔfADC contrasts are sensitive to early microstructural changes due to HI‐induced neurodegeneration in the studied regions. Conclusion The findings show that the frequency‐dependence of ADC measurements with oscillating‐gradient dMRI can provide a sensitive contrast to detect HI‐induced neurodegeneration in neuronal layers of the neonatal mouse hippocampus. Magn Reson Med 72:829–840, 2014. © 2013 Wiley Periodicals, Inc.